Efficacy of Cyombopogon Citratus Extract Against Enterococcus Faecalis - Permatasari Lahagu, Tessya Nitulo; Huynh Diem An; Cindy Denhara Wijaya; Mellisa Sim (Biomedical Journal of Indonesia, 2021)
Endodontic treatment refers to the act of removing infected pulp tissue and formingand reforming the root canals to prevent bacteria from entering the root canals.Microbial infection in the root canal or in the periapical area is a factor that can leadto failure of root canal treatments. Endodontic treatment failure can be caused thebacteria Enterococcus faecalis. The irrigation agent commonly used is sodiumhypochlorite. Sodium hypochlorite in large concentrations can be toxic to tissues.Lemongrass plant (Cymbopogon citratus) is a natural ingredient that can be used asan antibacterial agent. The aims of study to determine the comparison of theantibacterial effectiveness of lemongrass plant extracts (Cyombopogon citratus (DC).Staph) concentrations of 25%, 50%, 75%, 100% with 2.5% sodium hypochlorite ininhibiting the growth of the bacterium Enterococcus faecalis. Lemongrass plantextracts Cyombopogon citratus (DC). Staph) made by maceration method andconverted into 25%, 50%, 75%, and 100%. The bacterial test method used the agardiffusion test (Kirby-Bauer test) to see the effectiveness of antibacterialsThe result ofthe one way ANOVA statistical test resulted in significance value of p=0,001 (p<0,05)so that means there was differences in the average diameter of inhibitory lemongrassplant extracts (Cyombopogon citratus (DC). Staph) concentrations of 25%, 50%,75%, 100% with 2.5% sodium hypochlorite in inhibiting the growth of the bacteriumthe results are 13.68 ± 1.34 mm, 16.08 ± 0.87 mm, 16.33 ± 0.35 mm, 17.78 ± 0.93mm and 7.83 ± 0.44 mm and reinforced by the posthoc Tukey HSD test. Theconclusion from the study that there is a difference between the antibacterialeffectiveness of lemongrass plant extract (Cyombopogon citratus (DC). Staph)concentrations of 25%, 50%, 75% and 100% with 2.5% sodium hypochlorite ininhibiting the growth of the bacterium Enterococcus faecalis.